2015
DOI: 10.1016/j.jnutbio.2015.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Nutrigenomics analysis reveals that copper deficiency and dietary sucrose up-regulate inflammation, fibrosis and lipogenic pathways in a mature rat model of nonalcoholic fatty liver disease

Abstract: Nonalcoholic fatty-liver disease (NAFLD) prevalence is increasing worldwide, with the affected US population estimated near 30%. Diet is a recognized risk factor in the NAFLD spectrum, which includes non-alcoholic steatohepatitis (NASH) and fibrosis. Low hepatic copper (Cu) was recently linked to clinical NAFLD/NASH severity. Simple sugar consumption including sucrose and fructose is implicated in NAFLD, while consumption of these macronutrients also decrease liver Cu levels. Though dietary sugar and low Cu ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
30
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 72 publications
4
30
0
Order By: Relevance
“…ACLY uses citrate to produce acetyl‐CoA and that is subsequently used by FASN as well as for the synthesis of malonyl‐CoA by ACC. Thus, this enzyme links glycolysis with lipogenesis, and expression levels of ACLY have been correlated to the pathology of diseases like non‐alcoholic fatty liver disease (Wang et al, ; Tallino et al, ), type 2 diabetes (Guay et al, ; MacDonald et al, ), obesity, and to many cancers, including that of the breast (Szutowicz et al, ). Likewise, ACC is required for palmitate synthesis due to the use of malonyl‐CoA by FASN, in addition to the important regulatory functions of malonyl‐CoA in the cell, as previously mentioned.…”
Section: Oncogenic Antigen 519mentioning
confidence: 99%
“…ACLY uses citrate to produce acetyl‐CoA and that is subsequently used by FASN as well as for the synthesis of malonyl‐CoA by ACC. Thus, this enzyme links glycolysis with lipogenesis, and expression levels of ACLY have been correlated to the pathology of diseases like non‐alcoholic fatty liver disease (Wang et al, ; Tallino et al, ), type 2 diabetes (Guay et al, ; MacDonald et al, ), obesity, and to many cancers, including that of the breast (Szutowicz et al, ). Likewise, ACC is required for palmitate synthesis due to the use of malonyl‐CoA by FASN, in addition to the important regulatory functions of malonyl‐CoA in the cell, as previously mentioned.…”
Section: Oncogenic Antigen 519mentioning
confidence: 99%
“…Copper metabolism is important in a number of host functions, with diet and therapeutics under investigation for several genetic and developmental defects in rodent models [14, 51]. Here we show that cellular copper homeostasis is linked to the influenza A virus life cycle.…”
Section: Discussionmentioning
confidence: 71%
“…Copper is an important cofactor for a number of critical cellular processes, including cellular respiration and mitigation of oxidative stress. Many additional copper-dependent processes are observed in specific tissues, such as modulation of lipid metabolism in the liver [13, 14], and neurotransmitter processing in the brain [15, 16]. In the lung and respiratory tract, extracellular matrix synthesis requires the copper-containing enzyme lysyl oxidase [17].…”
Section: Introductionmentioning
confidence: 99%
“…This study also analyzed a rat model of NAFLD and revealed a histopathological response consistent with NAFLD in rats fed a CuD diet, supporting the link between CuD and hepatic dyslipidemia. Several other groups have reported NAFLD‐like symptoms in animal models fed diets deficient in copper, including transcriptomics analysis that found increased expression of transcripts associated with inflammation, fibrosis, and hepatic stellate cell activation, all consistent with NAFLD progression . More recently, a second clinical study confirmed the inverse correlation between hepatic copper content and the extent of steatosis , but also revealed the important finding that the correlation only held in patients without MetS.…”
Section: Copper Deficiency and Dietary Fructose Are Linked In Processmentioning
confidence: 82%
“…Marginal CuD has recently gained attention in a number of diseases including Alzheimer's disease, ischemic heart disease (IHD), non‐alcoholic fatty‐liver disease (NAFLD), and obesity . Many of these clinical manifestations have been linked with alterations in lipid metabolism and ultimately dyslipidemia , including abnormal cholesterol metabolism in Alzheimer's disease (recently reviewed here: ref.…”
Section: Insufficient Dietary Copper Increases Lipid Synthesismentioning
confidence: 99%